SINDROM AMNESTIK ORGANIK PADA ANAK DENGAN EPILEPSI - Tulus, Angelina; Ayu Trisna Windiani, I Gusti; Agung Ngurah Sugitha Adnyana, I Gusti; Ayu Indah Ardani, I Gusti (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2025)
Epilepsy is a chronic neurological disorder that can affect physical, cognitive, psychological, and social aspects in children. One of the prominent impacts is memory impairment, which in severe cases may develop into organic amnestic syndrome, particularly when accompanied by structural abnormalities such as hippocampal sclerosis. This article aims to report a case of organic amnestic syndrome in an adolescent with epilepsy and bilateral mesial temporal sclerosis, and to emphasize the importance of early detection and multidisciplinary management. The patient was a 15-year-old female adolescent with a history of generalized tonic-clonic epilepsy for the past two years and persistent memory complaints for six months. Cognitive assessment using the Indonesian version of the MoCA (MoCA-INA) showed a score of 19/30, and emotional evaluation using the CDI yielded a score of 19. Brain MRI revealed bilateral hippocampal atrophy, while EEG showed bilateral temporal epileptiform activity. The diagnosis was established based on clinical, neuropsychological, and radiological findings. The patient received combination therapy consisting of fluoxetine 10 mg/day, carbamazepine 300 mg twice daily, and supportive psychotherapy. The findings revealed a close association between epilepsy, hippocampal damage, memory impairment, and depressive symptoms. This case highlights the importance of structured memory screening and multidisciplinary intervention to minimize the cognitive and psychosocial impact of epilepsy in children and adolescents. ABSTRAK Epilepsi merupakan gangguan neurologis kronis yang dapat berdampak pada aspek fisik, kognitif, psikologis, dan sosial anak. Salah satu dampak yang menonjol adalah gangguan memori, yang pada kasus berat dapat berkembang menjadi sindrom amnestik organik, khususnya jika disertai kelainan struktural seperti sklerosis hipokampus. Artikel ini bertujuan melaporkan kasus sindrom amnestik organik pada remaja dengan epilepsi dan sklerosis mesial temporal bilateral, serta menekankan pentingnya deteksi dini dan manajemen multidisipliner. Pasien adalah remaja perempuan usia 15 tahun dengan riwayat epilepsi tonik-klonik umum sejak dua tahun terakhir dan keluhan gangguan memori menetap selama enam bulan. Pemeriksaan kognitif menggunakan MoCA-INA menunjukkan skor 19/30, dan penilaian emosional menggunakan CDI menghasilkan skor 19. MRI otak menunjukkan atrofi hipokampus bilateral, sementara EEG memperlihatkan aktivitas epileptiform di area temporal bilateral Diagnosis ditegakkan berdasarkan data klinis, neuropsikologis, dan radiologis. Pasien menerima terapi kombinasi berupa fluoxetine 10 mg/hari, carbamazepine 300 mg dua kali sehari, serta psikoterapi suportif. Temuan menunjukkan adanya hubungan erat antara epilepsi, kerusakan hipokampus, gangguan memori, dan gejala depresi. Kasus ini menggarisbawahi pentingnya skrining memori terstruktur dan intervensi multidisipliner untuk meminimalkan dampak kognitif dan psikososial epilepsi pada anak dan remaja.